Denials of the real distiction between the agent intellect and the possible in the XIVth century - Sellés, Juan Fernando (Anales del Seminario de Historia de la Filosofía, 2012)
In this work we study the nature of the agent intellect according four little known authors of the XIVth century: 1) Guillelmus de Alnwick. 2) Gregorius Ariminensis. 3) Thomas de Bailly. 4) Petrus de Ailly.